Aerosol deposition in the lungs of spontaneously breathing rats using Gd‐DOTA‐based contrast agents and ultra‐short echo time MRI at 1.5 Tesla. Issue 2 (24th March 2015) - Wang, Hongchen; Sebrié, Catherine; Ruaud, Jean‐Pierre; Guillot, Geneviève; Bouazizi, Khaoula; Willoquet, Georges; Maître, Xavier; Darrasse, Luc; de Rochefort, Ludovic
Abstract : Purpose: Aerosol toxicology and drug delivery through the lungs, which depend on various parameters, require methods to quantify particle deposition. Intrapulmonary‐administered MRI contrast agent combined with lung‐specific imaging sequences has been proposed as a high performance technique for aerosol research. Here, aerosol deposition is assessed using ultra‐short echo (UTE) sequences. Methods: Before and after administration of Gd‐DOTA‐based aerosol delivered nose‐only in free‐breathing healthy rats, a T1 ‐weighted 3D UTE sequence was applied in a clinical 1.5 Tesla scanner. Administration lasted 14 min, and the experiment was performed on six rats. A contrast‐enhanced quantitative analysis was done. Results: Fifty percent signal enhancement was obtained in the lung parenchyma. Lung clearance of the contrast agent was evaluated to be 14% per h (corresponding to a characteristic clearance time of 3.6 h) and aerosol deposition was shown to be homogeneous throughout the lung in healthy rats. The total deposited dose was estimated to be 1.05 µmol/kg body weight, and the concentration precision was 0.02 mM. Conclusion: The UTE protocol with nebulized Gd‐DOTA is replicable to significantly enhance the lung parenchyma and to map aerosol deposition. This functional strategy, applied in a clinical system with a clinical nebulization setup and a low inhaled dose, suggests a feasible translation to human. Magn Reson Med 75:594–605, 2016. © 2015 Wiley Periodicals, Inc.